SCREENING, DESIGN AND CHARACTERIZATION OF ALGAE-BASED TOPICAL DOSAGE FORM AS A REMEDY FOR DIGITAL AGEING - DASANKOPPA, FATIMA SANJERI; SAGARE, REVATI DHARAMPAL; SUREBAN, MEGHA N.; SHOLAPUR, HASANPASHA N.; RAMESH, ARUNKUMAR GUNDAIAH; MURUGESAN, VIJAYAKUMAR (International Journal of Applied Pharmaceutics, 2025)
Objective: To design and characterize algae-based topical dosage forms as a remedy for digital aging and to assess the compatibility and safety of the developed topical formulation through in-vitro studies. Methods: A Central Composite Design (CCD) was employed to systematically investigate the impact of stabilizer concentration, sonication amplitude, and time on the particle size and zeta potential of the formulations. Fourier Transform Infrared Spectroscopy (FTIR), Sun Protection Factor (SPF), and antioxidant activity of the drug were initially assessed. Different concentrations of phospholipid and ethanol were used to create the ethosomes. Size, surface charge, shape, and Entrapment Efficiency (EE) were used to develop and characterize the drug-containing ethosomes. After that, the improved ethosomes were added to create a topical gel formulation. It was tested for stability over three months by looking at its organoleptic, pH, viscosity, and Sun Protection Factor (SPF) activity. Results: The drug showed 78.94% efficacy in scavenging free radicals. The optimized ethosomes had a spherical form, particle size of 221.8 nm, surface charge is -28.21 mV, and a notable 99.36 % entrapment efficiency. The maximum Sun Protection Factor (SPF) activity was observed in the ethosomal gel EG2. Furthermore, the chosen topical gel held up well during the investigation. Conclusion: The objective of the study was to develop a stable and functionally effective gel by using suitable ingredients. The evaluation study of the developed gel showed good pH, antioxidant activity, and sun protection activity.